Constraints in household relocation: Modeling land-use/transport interactions that respect time and monetary budgets - Moeckel, Rolf (Journal of Transport and Land Use, 2016)
Traditionally, integrated land-use/transportation models intend to represent all opportunities of travel and household location, maximize utilities and find an equilibrium in which no person or household could improve their satisfaction any further. Energy scarcity, higher transportation costs, and an increasing share of low-income households, on the other hand, demand special attention to represent constraints that households face, rather than opportunities for utility maximization. The integrated land-use model SILO explicitly represents various constraints, including the price of a dwelling, the travel time to work, and the monetary transportation budget. SILO ensures that no household makes choices that violate these constraints. Implementing such constraints helps SILO to generate more realistic results under scenarios that put current conditions under a stress test, such as a serious increase in transportation costs or severely increased congestion.